Vitamin C prevents the effects of high rearing temperatures on the quality of broiler thigh meat - Ferreira, I. B. [UNESP]; Matos Junior, J. B. [UNESP]; Sgavioli, S. [UNESP]; Vicentini, T. I. [UNESP]; Morita, V. S. [UNESP]; Boleli, I. C. [UNESP] (Oxford Univ Press, 2015)
We investigated the effects of incubation temperatures and vitamin C injections into eggs (treatments: 37.5 degrees C, 39 degrees C, 39 degrees C+vitamin C) on resultant chick pectoralis major and sartorius muscle fiber hypertrophy, as well as their effects on the quality of breast and over-thigh meat of broilers reared under cold, control, or hot temperatures. Incubation at 39 degrees C increased the shear force and reduced meat redness in breast meat (P < 0.05). Vitamin C prevented these high temperature incubation effects [shear force (kgf cm(-2)): 37.5 degrees C = 2.34, 39 degrees C = 2.79, 39 degrees C+vitamin C = 2.44; redness: 37.5 degrees C = 2.64, 39 degrees C = 1.90, 39 degrees C+vitamin C = 2.30], but reduced water content (37.5 degrees C = 74.81%, 39 degrees C = 74.53%, 39 degrees C+vitamin C = 69.39%) (P < 0.05). Cold rearing temperatures increased breast meat redness (a*:cold = 2.78, control = 2.12, hot = 1.98), while hot rearing temperatures reduced the muscle fiber area (cold = 5.413 mu m(2), control = 5.612 mu m(2), hot = 4.448 mu m(2)) (P < 0.05) without altering meat quality (P > 0.05). Hot rearing temperatures increased the cooking loss (cold = 30.10%, control = 33.66%, hot = 37.01%), shear force (cold = 3.05 kgf cm(-2), control = 3.43 kgf cm(-2), hot = 4.29 kgf cm(-2)) and redness (a*:cold = 4.63, control = 3.55, hot = 3.20) in the over-thigh meat of broilers from eggs incubated at 37.5 degrees C, increasing the area of muscle fibers, while cold rearing temperatures diminished cooking loss and shear force, reducing the muscle fiber area (P < 0.05). Incubation at 39 degrees C and 39 degrees C+vitamin C prevented the effects of hot and cold rearing temperatures, by diminishing and increasing the muscle fiber area, respectively.
Keywords: Heat stress; Meat; Muscle growth; Poultry; Vitamin C